Locus of Control Moderates the Relationship Between Exposure to Bullying Behaviors and Psychological Strain - Reknes, Iselin; Visockaite, Gintare; Liefooghe, Andreas; Lovakov, Andrey; Einarsen, Ståle V. (Frontiers in Psychology, 2019)
Workplace bullying is regarded as one of the most devastating stressors at work for those targeted, and the bullying-mental health relationship is well-documented in the literature, even under lower levels of exposure. However, less is known about when and for whom these negative behaviors have more effect. Perceived control over outcomes in life (i.e., internal locus of control) has normally been related to good health and well-being, while relying on chance and/or powerful others (i.e., external locus of control) have been related to stress and poor health. In situations with reduced individual control like bullying, however, these mechanisms may act differently. Hence, the aim of the present study was to investigate whether internal- and external locus of control, respectively, moderates the bullying-mental health relationship. Data were gathered in 2014-2015 from 1474 Russian employees, and analyzed using the PROCESS macro SPSS supplement. Although the prevalence of high intensity bullying was low, the results showed the expected positive relationship between exposure to bullying behaviors and psychological strain. Furthermore, this relationship was moderated by locus of control. In line with our expectations, internal locus of control did not have the generally assumed positive effect on strain when exposed to bullying behaviors. On the other hand, external locus of control seems relatively beneficial when facing bullying behaviors. The results of this study thus support that exposure to bullying and its associated behaviors are unique stressors where personal characteristics seem to play a different role than normally expected when facing other kinds of stressors.